Financial Management in Surgical Departments: Balancing Cost, Quality, and Patient Care - Barqah Prantama, Muhammad; B. Venugopal, B. Venugopal; Gharpure, Yogesh; Inumula, Krishna Murthy; Sahu, Aradhana; Rajasekar G, Rajasekar G (Journal of Neonatal Surgery, 2025)
Balancing cost efficiency, technical developments, and patient care quality in surgical departments depends on good financial management. The approaches to maximize expenses including investment in innovative surgical technology, effective resource allocation, and cost management actions. To guarantee long-term financial viability while raising surgical accuracy and patient outcomes, hospitals must carefully assess the cost-benefit of robotic and AI-assisted operations. By lowering administrative tasks, guaranteeing proper payments, and thereby avoiding errors, the combination of digital health records and automated billing systems improves operational efficiency. Expanding surgical treatments through specialized programs and sophisticated operations also helps meet patient demand and create income. Reducing follow-up expenditures, enhancing post-surgical monitoring, and lowering hospital readmissions depend mostly on telemedicine integration. Transparency in invoicing and fair pricing are ethical and patient-centric financial ideas that guarantee surgical treatment accessibility while preserving economic stability. Using data-driven decision-making, streamlining surgical procedures, and implementing creative healthcare models can help hospitals to reach financial sustainability. A well-organized financial structure helps surgical departments to balance cost-effectiveness, high-quality treatment, and technical developments, so guaranteeing long-term development and better healthcare results.